Implementasi Sistem Informasi Geografis Dengan Metode Poligon Tertutup Untuk Menentukan Area Genangan Rob - Agus Ilyas; Tri Titiani Chasanah; Tri Agus Setiawan; Tri Pudji Wahjuningsih (JURIKOM (Jurnal Riset Komputer), 2022)
Pekalongan City is located on the north coast of Java Island and is in a lowland so it is prone to tidal disasters. Rob happened a few years ago, the longer it turns out that the more frequent and higher it is, this happens because of the massive land subsidence due to global warming so that sea levels rise. Land subsidence that occurs in Pekalongan, especially North Pekalongan, is classified as high per year around 10-34 cm. To solve the Rob problem The government built a giant embankment on the seashore that is expected to inhibit or reduce the rob. Areas that were originally affected by the tidal with the presence of this giant embankment can be reduced, including bandengan, Pasirsari, Customs, Panjang Baru, Panjang Wetan, Pasir Kramat Kraton and Slamaran villages. The problem in this study is that so far there has been no digital map that depicts the rob area and changes in the location of the rob area in the city of Pekalongan. This research was carried out using the Research and Development (R&D) method, a system development method using Waterfall. To describe the rob area using polygons and to depict the map using google earth, as for determining the coordinates of the location using Latitude and Longitude. Data collection using Observations, Interviews and Questionnaires. The purpose of this study is to make a Geographic Information System application mapping rob areas and their changes based on year criteria with Web-based multi-layer in Pekalongan City. The results of this polygon depiction are stored in a KML file and are expected to be a solution for structuring the area, especially the coastal part and for the community is expected to be better prepared to face disasters